ASPEK PIDANA TERHADAP PEJABAT PEMBUAT AKTA TANAH (PPAT) SEBAGAI PEJABAT UMUM - Ipung, Taifah; yasarman, yasarman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Today's economic development has improved land law relations towards an increasingly complex situation. the use of land today has led to multifunctionality is not as simple as when Law No. 5 of 1960 on agrarian regulations and principles promulgated. Indonesia today is undergoing a shift and has stepped on the era of economic takeoff, the land is not only used for agricultural land but for the benefit and even become an object of business thus the forms of transition rights are diverse and complex. The passive attitude of PPAT in serving the parties in the sense of accepting only all data and information submitted to it without carefully researching the truth of the data or information, is an opportunity for certain parties to apply data or information that is not true or false to the creation of a land deed. PPAT as the official of the land deed maker at the request of certain parties enter data or information that is not true or False into the deed made in exchange for services and the inclusion of false or false information is an agreement between PPAT.